Anchoring spinel cobalt and zinc ferrites on zeolite for highly synergic photocatalytic reduction of chromium (VI) - Moin Mehrbakhsh; Moones Honarmand; Ahmad Aryafar (Scientific Reports)
Abstract To tackle the challenges of increasing the efficiency of photocatalysts, a ternary magnetic heterojunction photocatalyst containing spinel cobalt and zinc ferrites, and zeolite (CZZ) was designed and fabricated. The physicochemical properties of the novel photocatalyst were verified using characterization techniques such as XRD, FT-IR, FE-SEM, EDS mapping, N2 adsorption-desorption, VSM, PL, and UV–Vis DRS. The CZZ photocatalyst exhibited a significant Cr (VI) reduction rate of 0.1535 min−1, which was 9.27, 5.37 and 3.58 times higher than those of single ZnFe2O4 nanoparticles (0.0166 min−1), CoFe2O4 nanoparticles (0.0286 min−1), and CoFe2O4–ZnFe2O4 (0.0428 min−1) respectively. CZZ showed an excellent reusability after three consecutive cycles of Cr(VI) reduction. The results from the experiments in different aqueous environments displayed that CZZ could be a promising photocatalyst to reduce Cr(VI) in the treatment of actual aqueous matrices. The present study not only provides a highly active catalytic system for the practical removal of Cr(VI) but also paves the way for the fabrication of high-performance heterojunction photocatalysts.